Focusing on dissociated motor development in Brazilian children - Minami Maria Avanise Yumi; Funayama Carolina A.R.; Daneluzzi Julio Cesar (Arquivos de Neuro-Psiquiatria)
Dissociated motor development (DMD) is considered when the baby starts independent walking late, with normality of the other fields of development. There is evidence that babies with DMD present an atypical crawling pattern and hypotonia. To investigate the frequency and characteristics of DMD, neurological examination was performed monthly in 177 healthy full-term babies from 6 months age, in urban and rural zone samples in Brazil. Among 20 children with atypical crawling, none presented hypotonia neither did they start independent walking late. The means of the ages at the begining of atypical crawling and independent walking acquisitions, 7.40mo (SD 1.4) and 12.76mo (SD 2.5) respectively, did not differ from the group with crossed crawling pattern. Thus, in this sample of Brazilian healthy children we did not find cases with DMD.